2021 Comprehensive Surveillance Review : Background Paper on Integrating Climate Change into Article IV Consultations. (Policy Papers; Policy Paper ;, 2021)
While the IMF has been involved in the climate debate since at least 2008, a systematic account of how to integrate climate change into surveillance has been lacking to date. This paper seeks to fill the gap. It argues that domestic policy challenges related to climate change-such as adaptation efforts for climate vulnerable countries, or policies to deliver a country's Nationally Determined Contribution under the Paris climate accord-are covered by the IMF's bilateral surveillance mandate and therefore valid topics for Article IV consultations wherever these challenges cross the threshold of macro-criticality. Climate change mitigation is a global policy challenge and therefore falls under multilateral surveillance. The paper proposes a pragmatic approach that focusses especially on the mitigation efforts of the 20 largest emitters of greenhouse gases.